Activity Test Of Ethanol and n-Hexane Fraction Of African Leaves (Vernonia amygdalina Delile) as Antihyperuricemia On Male Mice Induced by Potassium Oksonat - Deni Karisnawati; Saibun Sitorus; Chairul Saleh (PROSIDING SEMINAR KIMIA, 2015)
Antihyperuricemia activity tests have conductedon aethanolandn-hexane fraction Africanleaves (Vernonia amygdalina Delile). Hyperuricemia is a condition in which uric acid levels in the blood increases due to the high consumption of purine converted to uric acid by xanthine oxidase. Antihyperuricemia activity test of ethanolic and n-hexane fraction of African leaves (Vernonia amygdalina Delile) conducted on male white mice with variation in doses of 6, 11 and 22 mg/kg BW and variation of measurement time of 1, 2, 3 and 4 hours after administration of the extract orally. Data were analyzed with ANOVA and continued with Duncan test. Ethanolic fraction 11 mg/kg is the most effective fraction lower uric acid levels by 54.62% compared to alupurinol 300 mg/kg BW which lower uric acid levels by 56.91%. Phytochemical screening showed that the ethanolic fraction of African leaves contains triterpenoids, steroids, phenolics, flavonoids and saponins whereas n-hexane fraction containing alkaloids, steroids and flavonoids. These results show the extracts of African leaves have antihiperurisemia activity.